Decatecholaminization of Septic Shock Patients in Intensive Care Unit: an Economic Assessment in the Italian Setting - Alfredo Del Gaudio; Assunta Caiazza; Luana Bortone; Sonia Tomasso; Ilaria Bozzari; Laura Vincenzi; Gianluca Furneri; Luigi Tritapepe (Farmeconomia: Health Economics and Therapeutic Pathways)
INTRODUCTION: Prolonged administration of norepinephrine to critically ill patients can lead to serious adverse events. In this context, the concept of “decatecholaminization” has emerged over the past decade, involving the association of vasopressin with norepinephrine to reduce catecholamines need. Additionally, beta-blockers can help prevent increased heart rate resulting from sepsis treatments. This study presents an economic analysis evaluating the economic implications of the decatecholaminization use in patients with septic shock treated in intensive care unit (ICU) from the Italian National Health Service (NHS) perspective.